David du Plessis and the Assemblies of God: the struggle for the soul of a movement - Ziefle, Joshua R. (Global Pentecostal and charismatic studies, 2013)
I. A practical pentecost : Primitivism, pragmatism, and pentecostalism ; Problematic pentecostal beginnings ; Early controversies -- II. The path of pentecost : Du Plessis's formative years ; Worldwide pentecostal dialogue ; Du Plessis meets the ecumenical movement ; 1959 A year of hope and promise -- III. Irreconcilable pentecosts : The challenges of pentecostal growth ; The Assemblies of God dismisses Du Plessis ; Du Plessis in the aftermath -- IV. Not Babel, but pentecost : Ecumenism and the roots of the charismatic movement ; The charismatic movement in mainline protestantism ; Charismatic renewal in the Roman Catholic church -- V. Pentecost set free? : The ecumenism if the charismatic movement ; The Assemblies of God and the charismatics ; Interpreting the Assemblies of God's changing perspective ; The continuing mission of David J. du Plessis -- Conclusion: the lessons of pentecost